Production of Human Cu, Zn SOD with Higher Activity and Lower Toxicity in E. coli via Mutation of Free Cysteine Residues. (16th February 2017) - Zhang, Kun; Zhang, Yuejuan; Zi, Jing; Xue, Xiaochang; Wan, Yi
Abstract : Although, as an antioxidant enzyme, human Cu, Zn superoxide dismutase 1 (hSOD1) can mitigate damage to cell components caused by free radicals generated by aerobic metabolism, large-scale manufacturing and clinical use of hSOD1 are still limited by the challenge of rapid and inexpensive production of high-quality eukaryotic hSOD1 in recombinant forms. We have demonstrated previously that it is a promising strategy to increase the expression levels of soluble hSOD1 so as to increase hSOD1 yields in E. coli . In this study, a wild-type hSOD1 (wtSOD1) and three mutant SOD1s (mhSOD1s), in which free cysteines were substituted with serine, were constructed and their expression in soluble form was measured. Results show that the substitution of Cys111 (mhSOD1/C111S) increased the expression of soluble hSOD1 in E. coli whereas substitution of the internal Cys6 (mhSOD1/C6S) decreased it . Besides, raised levels of soluble expression led to an increase in hSOD1 yields. In addition, mhSOD1/C111S expressed at a higher soluble level showed lower toxicity and stronger whitening and antiradiation activities than those of wtSOD1. Taken together, our data demonstrate that C111S mutation in hSOD1 is an effective strategy to develop new SOD1-associated reagents and that mhSOD1/C111S is a satisfactory candidate for large-scale production.